2017
DOI: 10.1155/2017/5646390
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Clarity and Visual Outcomes after Small-Incision Lenticule Extraction and Comparison to Femtosecond Laser-Assisted In Situ Keratomileusis

Abstract: Purpose. To evaluate corneal clarity and visual outcomes after small-incision lenticule extraction (SMILE) and compare them to femtosecond laser-assisted in situ keratomileusis (FS-LASIK). Materials and Methods. Fifty-eight myopic eyes of 33 patients who underwent SMILE were compared to 58 eyes of 33 patients treated with FS-LASIK. All procedures were performed using VisuMax® femtosecond laser and MEL 80® excimer laser (Carl Zeiss Meditec AG, Germany). Pentacam™ (Oculus, Germany) was used for pre- and 3-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
4
27
1
Order By: Relevance
“…The proposed method may enhance the quality of the surgical result of SMILE by providing assistance in nomograms and preventing the misdiagnosis in nomograms. Considering that less surgical experience in SMILE can cause signi cant in ammatory response and tissue trauma, 28,29 a referential nomogram guide for ophthalmologists with less experience with the proposed method may be bene cial.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method may enhance the quality of the surgical result of SMILE by providing assistance in nomograms and preventing the misdiagnosis in nomograms. Considering that less surgical experience in SMILE can cause signi cant in ammatory response and tissue trauma, 28,29 a referential nomogram guide for ophthalmologists with less experience with the proposed method may be bene cial.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no comprehensive report describing the AD or LT difference between LASIK and SMILE, but some differences have been reported. Lazaridis A et al 14 compared the corneal clarity and visual outcomes between FS-LASIK and SMILE, reporting that the preoperative mean spherical equivalent refraction did not show a significant difference (-4.80 ± 2.4 D and -5.51 ± 1.86 D, respectively; p = 0.136), but the mean estimated LT was significantly thicker in the SMILE group (99 ± 38 µm and 116 ± 28 µm, respectively; p = 0.017). Wang et al 15 reported postoperative differences in the degree of corneal biomechanical change between SMILE and LASIK, where the estimated LT was significantly thicker in the SMILE group when the spherical equivalent refraction was less than -6.0 D even if there was no significant difference in preoperative spherical equivalent refraction and postoperative biomechanical strength of cornea between 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no comprehensive report describing the AD or LT difference between LASIK and SMILE, but some differences have been reported. Lazaridis A et al 15 compared the corneal clarity and visual outcomes between FS-LASIK and SMILE, reporting that the preoperative mean spherical equivalent refraction did not show a significant difference (-4.80 ± 2.4 D and -5.51 ± 1.86 D, respectively; p = 0.136), but the mean estimated LT was significantly thicker in the SMILE group (99 ± 38 µm and 116 ± 28 µm, respectively; p = 0.017). Wang et al 16 reported postoperative differences in the degree of corneal biomechanical change between SMILE and LASIK, where the estimated LT was significantly thicker in the SMILE group when the spherical equivalent refraction was less than -6.0 D even if there was no significant difference in preoperative spherical equivalent refraction and postoperative biomechanical strength of the cornea between the two groups.…”
Section: Discussionmentioning
confidence: 99%